Local policy and its impact on the performance of the province of Baghdad. - حسين فرح ضياء; امين محمد عبد الله (Journal of Economics and Administrative Sciences, 2017)
Abstract The current research aims to clarify the role of local policies on the performance of the province of Baghdad, after studies proved practical experience what those policies of the major role and effect on the lives of citizens, as well as alleviate the burden on central government, which make a lot of states give local governments broad powers and her specialty funds for the exercise of its vital role and actor in various joints of local development, research has indentified a problem in a number of questions such as: do you have the policy of the provincial council of local qualified and able to influence the performance of the province? What are the main forces of powerful and implementation of policies at all level? Is there a conflict between the public policy of the state and the policy of local government? In order to achieve the goal of the research and answer the questions the problem has been studied through the analysis of the information collected in theory and in practice by a lot of statistical methods and a statement effect relationships and the correlation between variables and the dimensions of the current study, and was the study sample is limited to members of the Board conservative (Baghdad province) to be considered elected by the local audience, as well as makers of local politics within the province according to the law of the provincial councils is not organized in a region No. 21 of 2008, the researcher used a questionnaire to collect data in the research said, saluting the total study sample (58) member members of the provincial council were retrieved (46) a questionnaire from the total number mentioned to the number of members of the council, where the section of this research into four sections the first devoted to the methodology of the study, and the second devoted to the side of the theoretical, and the third on the practical side, the fourth topic was the conclusions and recommendation